(untitled) (Kawalu: Journal of Local Culture, 2024)
A state is often described as something complex that includes the executive, legislative, judicative, its people who belong to various religions and ethnicities with diverse social-economic problems, and its relation with other states such as sharing socio-economic borders, and other affairs. In this book Jan Newberry attempts to investigate a state through the eyes of mothers who get involved in the Indonesian Family Welfare Movement, known in Indonesia as Pembina Kesejahteraan Indonesia (PKK), in a village in Yogyakarta called Rumah Putri.